If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(n+10)=-3(n+10)+6n
We move all terms to the left:
9(n+10)-(-3(n+10)+6n)=0
We multiply parentheses
9n-(-3(n+10)+6n)+90=0
We calculate terms in parentheses: -(-3(n+10)+6n), so:We get rid of parentheses
-3(n+10)+6n
We add all the numbers together, and all the variables
6n-3(n+10)
We multiply parentheses
6n-3n-30
We add all the numbers together, and all the variables
3n-30
Back to the equation:
-(3n-30)
9n-3n+30+90=0
We add all the numbers together, and all the variables
6n+120=0
We move all terms containing n to the left, all other terms to the right
6n=-120
n=-120/6
n=-20
| -2-5k=2-3k | | -2n+1-19n=-20n-17 | | -(x-6)-7x=30-4x | | 23+3x=(x+8) | | 71=n/7+62 | | -4+7j=-4-4j | | 273=7(2n=3) | | 5x+7x-18=66 | | (8)=5-9x | | 16+2n=4-n | | p-6/2=2 | | p(3p+2)(p-4)=0 | | x+6+89+40=180 | | 1/3y-16=2 | | 3(3x+5)=7x-3 | | -6(5x+3)=132 | | -4(6+v)=-80 | | (5x-3x)/3=-22 | | 2x+x+10=37 | | -5n=–6n+8 | | 6x-15+x+15=5x+10 | | -10p-12=16-3p | | 3(2x+5)+4x=96 | | -4(3-x)=12 | | -3x+18=78+7x | | 2h=-3-h | | 39=13(14-x) | | -s-1=s-21 | | −26/33=13/11x | | 5(x-4)-3=-23 | | 252=204-x | | 14=3+5x-4 |